2009
DOI: 10.1186/1751-0147-51-32
|View full text |Cite
|
Sign up to set email alerts
|

Effect of yeast culture on milk production and metabolic and reproductive performance of early lactation dairy cows

Abstract: Background: The main objective of this study was to estimate the effect of supplementation with Saccaromyces cerevisiae (SC) (Yea-Sacc ® 1026) on milk production, metabolic parameters and the resumption of ovarian activity in early lactation dairy cows.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
20
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 40 publications
9
20
3
Order By: Relevance
“…This result is consistent with that of previous studies, which reported enhanced milk protein due to SC (Piret, Toomas, Andres, Raivo, & Kalle, 2009) and BS (Sun et al, 2013). This result is consistent with that of previous studies, which reported enhanced milk protein due to SC (Piret, Toomas, Andres, Raivo, & Kalle, 2009) and BS (Sun et al, 2013).…”
Section: Milk Yield and Compositionsupporting
confidence: 93%
See 1 more Smart Citation
“…This result is consistent with that of previous studies, which reported enhanced milk protein due to SC (Piret, Toomas, Andres, Raivo, & Kalle, 2009) and BS (Sun et al, 2013). This result is consistent with that of previous studies, which reported enhanced milk protein due to SC (Piret, Toomas, Andres, Raivo, & Kalle, 2009) and BS (Sun et al, 2013).…”
Section: Milk Yield and Compositionsupporting
confidence: 93%
“…In the present study, milk protein also increased in the SC, BS and mixed groups. This result is consistent with that of previous studies, which reported enhanced milk protein due to SC (Piret, Toomas, Andres, Raivo, & Kalle, 2009) and BS (Sun et al, 2013). There were some differences in DMI and milk performance between different probiotic treatments.…”
Section: Milk Yield and Compositionsupporting
confidence: 93%
“…This finding came in agreement with some previous studies referring that the calving -first service and calving -conception intervals were shorter in cattle supplemented by yeast culture than those nonsupplemented (Abdel-Khalek, 2003;Ibrahim, 2004;Komonna, 2007;Abdel-Rahman et al, 2012;Mousa et al, 2012;Ramosi et al, 2012). Such finding might be attributed either to stimulation of the immune system (Rodrigues et al, 2000;Young, 2012) or improvement of the health condition of the supplemented cows by yeast culture (Kalmus et al, 2009).…”
Section: Disscussionsupporting
confidence: 92%
“…This observation agrees with the shortened interval from parturition to effective mating of New-Zealand×Californian rabbit does with Toyocerin ® observed by Nicodemus et al (2004). On the other hand, it contrasted with the results of Kalmus et al (2009), who reported no effect of yeast supplementation on resumption of ovarian activity in dairy cows. Our results showed that fertility of rabbits does improved in the S group during the 2 nd cycle compared to the first one (92.3 to 95.8%.…”
Section: Fertility Of Rabbit Doessupporting
confidence: 88%